Gold Nanoparticles Disrupt the IGFBP2/mTOR/PTEN Axis to Inhibit Ovarian Cancer Growth. Issue 31 (14th September 2022) - Hossen, Md. Nazir; Wang, Lin; Dwivedi, Shailendra Kumar Dhar; Zhang, Yushan; Rao, Geeta; Elechalwar, Chandra Kumar; Sheth, Vinit; Dey, Anindya; Asfa, Sima; Gulla, Suresh Kumar; Xu, Chao; Fung, Kar‐Ming; et al.
Abstract: By exploiting the self‐therapeutic properties of gold nanoparticles (GNPs) a molecular axis that promotes the growth of high‐grade serous ovarian cancer (HGSOC), one of the deadliest gynecologic malignancies with poorly understood underlying molecular mechanisms, has been identified. The biodistribution and toxicity of GNPs administered by intravenous or intraperitoneal injection, both as a single dose or by repeated dosing over two weeks are first assessed; no biochemical or histological toxicity to vital organs is found. Using an orthotopic patient‐derived xenograft (PDX) model of HGSOC, the authors then show that GNP treatment robustly inhibits tumor growth. Investigating the molecular mechanisms underlying the GNP efficacy reveals that GNPs downregulate insulin growth factor binding protein 2 (IGFBP2) by disrupting its autoregulation via the IGFBP2/mTOR/PTEN axis. This mechanism is validated by treating a cell line‐based human xenograft tumor with GNPs and an mTOR dual‐kinase inhibitor (PI‐103), either individually or in combination with GNPs; GNP and PI‐103 combination therapy inhibit ovarian tumor growth similarly to GNPs alone. This report illustrates how the self‐therapeutic properties of GNPs can be exploited as a discovery tool to identify a critical signaling axis responsible for poor prognosis in ovarian cancer and provides an opportunity to interrogate the axis to improve patient outcomes. Abstract : Gold nanoparticles inhibit insulin growth factor binding protein 2 (IGFBP2) secretion and expression by disrupting the IGFBP2/mTOR/PTEN axis.